Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Indihome - Musdalifah, Musdalifah; Tijjang, Bakhtiar; Lukman, Siti Diva Syarifah; Rifani, Riza Amalia (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to determine the effect of product quality and service quality partially and simultaneously have a positive and significant effect on customer satisfaction Indihome Parepare City. The research method used is the quantitative method, using primary data sourced from the results of distributing questionnaires to 90 samples that have been answered by respondents. The analysis technique used includes validity and reliability tests, hypothesis testing in the form of a simultaneous significant test (f test) and partial significance test (t test), multiple linear regression tests and also the coefficient of determination test (R2 test) using the IBM SPSS 25 program.The results of this study indicate that all questionnaire statements in the three variables (product quality, service quality and customer satisfaction) are declared valid and reliable. By testing the hypothesis showing that partially and simultaneously product quality and service quality have a positive and significant effect on customer satisfaction Indihome Kota Parepare